The value of non-invasive prenatal testing: preferences of Canadian pregnant women, their partners, and health professionals regarding NIPT use and access - Stanislav Birko; Vardit Ravitsky; Charles Dupras; Jessica Le Clerc-Blain; Marie-Eve Lemoine; Aliya O. Affdal; Hazar Haidar; Anne-Marie Laberge (BMC, 2019)
Abstract Background Canadian policies regarding the implementation and public coverage of non-invasive prenatal testing (NIPT) are heterogeneous and shifting, with NIPT being publicly covered for high-risk pregnancies in some provinces, but not others. Such a diverse and evolving policy landscape provides fertile ground for examining the preferences of pregnant women, their partners, and health professionals regarding the implementation and coverage of NIPT by the public healthcare system, as well as the factors influencing their preferences, which is what the present study does. Methods In this paper, we report the results of three-large scale Canadian surveys, in which 882 pregnant women, 395 partners of pregnant women, and 184 healthcare professionals participated. Results The paper focuses on preferences regarding how and when NIPT should be used, as well as the factors influencing these preferences, and how coverage for NIPT should be provided. These are correlated with respondents' levels of knowledge about Down syndrome and testing technologies and with their stated intended use of NIPT results. Conclusion Salient is the marked difference between the preferences of prospective parents and those of healthcare professionals, which has potential implications for Canadian policy regarding NIPT implementation and insurance coverage.